2020
DOI: 10.1097/eja.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine for the prevention of spinal-induced hypotension during caesarean delivery under combined spinal–epidural anaesthesia

Abstract: BACKGROUND During caesarean delivery under spinal anaesthesia hypotension may be managed by norepinephrine in preference to phenylephrine due a perception of less bradycardia and fewer reductions in cardiac output. OBJECTIVE As the optimum prophylactic dose of norepinephrine is unclear, we aimed to investigate its dose–response for preventing postspinal hypotension in caesarean delivery. DESIGN A randomised,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 17 publications
3
35
3
1
Order By: Relevance
“…In the current study, the incidence of postspinal anesthesia hypotension was as high as 68.42% (13/19) without using a prophylactic measure. Similar results were also reported in our previous study (62.24%, 61/98) 10 and by Wei et al 13 (70.00%, 14/20). Postspinal anesthesia hypotension remains a common complication during cesarean section with spinal anesthesia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, the incidence of postspinal anesthesia hypotension was as high as 68.42% (13/19) without using a prophylactic measure. Similar results were also reported in our previous study (62.24%, 61/98) 10 and by Wei et al 13 (70.00%, 14/20). Postspinal anesthesia hypotension remains a common complication during cesarean section with spinal anesthesia.…”
Section: Discussionsupporting
confidence: 93%
“…The ED50, ED85, and ED95 values for a prophylactic dose of norepinephrine were 0.029 (95% CI 0.008–0.042), 0.068 (95% CI 0.055–0.099), and 0.105 (95% CI 0.082–0.172) µg/kg/min, respectively. A loading bolus of 6 μg norepinephrine was given before norepinephrine infusion, and only bupivacaine was administrated for spinal anesthesia in our study; however, we found similar results, though different prophylactic doses were employed by Wei et al 13 The prophylactic doses of norepinephrine employed in our study was in accordance with Hasanin et al 7 and Fu et al 12 Significantly, the work reported by Hasanin et al 7 provided us a good foundation without exploring the ED50 and ED90 values. In addition, we further explored the overall stability of SBP control versus baseline, including MDPE and MDAPE.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The incidence of maternal hypotension in our patients was 38%. This incidence is similar to the incidence which was reported by Wei et al who used the same dose of NE infusion [12]. However, this incidence was relatively higher than that reported in our previous studies about cesarean delivery (∼ 30%) [5,6,13].…”
Section: Discussionsupporting
confidence: 89%
“…Two recent studies had suggested higher doses (0.07 mcg. Kg − 1 .min − 1 [12] and 0.08 mcg. Kg − 1 .min − 1 [18]); however, these studies were not available when we started our study.…”
Section: Discussionmentioning
confidence: 99%